Evaluation of a Multifunctional Polyvinylpyrrolidone/Hyaluronic Acid-Based Bilayer Film Patch with Anti-Inflammatory Properties as an Enhancer of the Wound Healing Process - Marco Contardi; Maria Summa; Pasquale Picone; Ornella Roberta Brancato; Marta Di Carlo; Rosalia Bertorelli; Athanassia Athanassiou (MDPI AG, 2022)
The management of acute and chronic wounds is still a socioeconomic burden for society due to the lack of suitable tools capable of supporting all the healing phases. The exponential spread of diabetes worldwide and the consequent increase of complicated diabetic ulcers require further efforts to develop scalable, low-cost, and easy-to-use treatments for tackling this emergency. Recently, we explored the fabrication of a polyvinylpyrrolidone/hyaluronic acid-based bilayer wound dressing, characterizing its physicochemical features and detailing its excellent antimicrobial activity. Here, we further demonstrate its biocompatibility on fibroblasts, keratinocytes, and red blood cells. The bilayer shows anti-inflammatory properties, statistically reducing the level of IL-6, IL-1β, and TNF-α, and a capacity to accelerate wound healing in vitro and in healthy and diabetic mice models compared to untreated mice. The outcomes suggest that this bilayer material can be an effective tool for managing different skin injuries.